A Criminal Law Review of the Practice of Withholding Employees' Diplomas in the Workplace as a Form of Collateral - Peale, Norman; Kristanto, Kiki; Setyobowo Sangalang, Rizki (Dinasti Research, 2025)
The practice of withholding employees' diplomas as collateral for employment is a common issue in Indonesia. This action has sparked controversy as it is considered a violation of human rights and the Labor Law. This study aims to analyze the criminal law regulations related to the practice of diploma withholding and assess the legal accountability of companies engaging in this practice. The research method used is normative juridical with a literature review approach. The findings indicate that withholding diplomas can be categorized as a criminal offense, especially if done in a way that harms employees or violates their right to seek better employment opportunities. Companies that withhold diplomas may be charged under the Criminal Code (KUHP) for unpleasant acts or embezzlement. This study recommends stronger law enforcement and awareness programs for workers regarding their rights to prevent the practice of diploma withholding.